Motivasi dalam Meningkatkan Kreativitas Mengajar Tutor di Lembaga Bimbingan Belajar Asieq Educare - Rohimah Aprilia Irawati (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This research was designed with the aim of examining in depth the motivation in increasing the teaching creativity of tutors at the ASIEQ Educare tutoring institution. This research used qualitative methods with a descriptive research model by describing objects as they are. The research results show that motivation in increasing the teaching creativity of tutors at the ASIEQ Educare tutoring institution can be said to be good. This can be seen from the system created by the institution so that it can bring out the enthusiasm or intrinsic motivation and extrinsic motivation that tutors have in teaching so that the tutor's creativity in teaching also increases. Apart from that, the model used by the ASIEQ Educare tutoring institution in motivating its tutors is to use a human resources model which focuses on providing feedback not only obtained through material but also immaterial things and meaningfulness in teaching as well as supporting motivation which can increase the teaching creativity of tutors in ASIEQ Educare tutoring agency. The strategies used by the ASIEQ Educare tutoring institution include; a) get to know all members of the ASIEQ Educare family well, b) assign tutors according to their respective interests and abilities, c) all members of the ASIEQ Educare family are considered work friends, d) activate regular discussions in order to carry out self-development with each other in the learning process.